Not giving up on people: a feminist case for prison abolition - Emerick, Barrett (Rowman & Littlefield, 2024)
"This book argues for prison abolition within the framework of feminist philosophy. Based in the Anglo-American, analytic tradition, the authors also draw on non-analytic sources, historical sources, and activist writing. The authors argue for a multi-generational collective action to build resilient communities that support the wellbeing of all"--